(untitled) (Baghdad Science Journal, 2025)
To demonstrate the effect of changing cavity length for FM mode locked on pulse parameters and make comparison for both dispersion regime , a plot for each pulse parameter as Lr function are presented for normal and anomalous dispersion regimes . The analysis is based on the theoretical study and the results of numerical simulation using MATLAB. The effect of both normal and anomalous dispersion regimes on output pulses is investigate Fiber length effects on pulse parameters are investigated by driving the modulator into different values. A numerical solution for model equations using fourth-fifth order, Runge-Kutta method is performed through MATLAB 7.0 program. Fiber length effect on pulse parameters is investigated by driving the modulator into different values of lengths. Result shows that, the output pulse width equals to ?= 501ns anomalous regime and ?=518ns in normal regime.